VALUES CREATED BY MUSIC EDUCATION IN GENERAL COMPREHENSIVE SCHOOLS - Läänemets, Urve; Kalamees-Ruubel, Katrin; Kiilu, Kristi; Kaja, Kadi; Sepp, Anu (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
This is the final part of research started in 2014 when development of the new National Curricula (NC) was initiated. The role of music education had to be mapped to prove its meaning as a traditional mandatory subject in the NC. According to the research program, different aspects, related to music education (content, integration of art subjects, informal and non-formal music activities, supportive learning environments, etc.), were analysed. The research of 2020 is summarising the values music education can provide for development of educated, responsible, ethical and creative people. The data collected from essays of school students and (future and in-service) music teachers (n=166), were analysed by qualitative methods. The values were classified by the following categories: social, cultural, cognitive, moral, aesthetic, personal. The research results can be used as arguments for developing music education syllabi in the NCs from kindergartens to gymnasia. The whole program of research is already being used for further development of music teacher education.